Scaffold of Selenium Nanovectors and Honey Phytochemicals for Inhibition of Pseudomonas aeruginosa Quorum Sensing and Biofilm Formation - Prateeksha,; Singh, Braj R.; Shoeb, M.; Sharma, S.; Naqvi, A. H.; Gupta, Vijai K.; Singh, Brahma N. (Frontiers in Cellular and Infection Microbiology, 2017)
Honey is an excellent source of polyphenolic compounds that are effective in attenuating quorum sensing (QS), a chemical process of cell-to-cell communication system used by the opportunistic pathogen Pseudomonas aeruginosa to regulate virulence and biofilm formation. However lower water solubility and inadequate bioavailability remains major concerns of these therapeutic polyphenols. Its therapeutic index can be improved by using nano-carrier systems to target QS signaling potently. In the present study, we fabricated a unique drug delivery system comprising selenium nanoparticles (SeNPs; non-viral vectors) and polyphenols of honey (HP) for enhancement of anti-QS activity of HP against P. aeruginosa PAO1. The developed selenium nano-scaffold showed superior anti-QS activity, anti-biofilm efficacy, and anti-virulence potential in both in-vitro and in-vivo over its individual components, SeNPs and HP. LasR is inhibited by selenium nano-scaffold in-vitro. Using computational molecular docking studies, we have also demonstrated that the anti-virulence activity of selenium nano-scaffold is reliant on molecular binding that occurs between HP and the QS receptor LasR through hydrogen bonding and hydrophobic interactions. Our preliminary investigations with selenium-based nano-carriers hold significant promise to improve anti-virulence effectiveness of phytochemicals by enhancing effective intracellular delivery.